Geniposide Balances the Redox Signaling to Mediate Glucose-Stimulated Insulin Secretion in Pancreatic β-Cells - Liu C (Dove Medical Press, 2020)
Chunyan Liu, Yanan Hao, Fei Yin, Jianhui Liu Chongqing Key Laboratory of Medicinal Chemistry & Molecular Pharmacology, Chongqing University of Technology, Chongqing 400054, People’s Republic of ChinaCorrespondence: Jianhui Liu; Fei YinChongqing Key Laboratory of Medicinal Chemistry & Molecular Pharmacology, Chongqing University of Technology, Hongguang Road 69, Ba’nan District, Chongqing 400054, People’s Republic of ChinaTel/Fax +86-23-6256-3182Email jhliu@cqut.edu.cn; fyin@cqut.edu.cnPurpose: To investigate the effect of geniposide on the biosynthesis of insulin and the expression protein disulfide isomerase (PDI) and endoplasmic reticulum oxidoreductin 1 (ERO1) in the presence of low (5 mM) and high (25 mM) glucose in pancreatic β cells.Methods: The content of insulin was measured by ELISA, the number of SH groups was determined with the classical chromogenic reagent, 5,5ʹ-dithiobis-(2-nitrobenzoic) acid (DTNB; also known as Ellman’s reagent), the expressions of PDI and ERO1 were analyzed by Western blot.Results: Geniposide played contrary roles on the accumulation of H 2O 2, the ratio of GSH/GSSG and the thiol–disulfide balance in the presence of low (5 mM) and high (25 mM) glucose in rat pancreatic INS-1 cells. Geniposide also regulated the protein levels of protein disulfide isomerase (PDI) and endoplasmic reticulum oxidoreductin1 (ERO1), the two key enzymes for the production of H 2O 2 during the biosynthesis of insulin in INS-1 cells.Conclusion: Geniposide affects glucose-stimulated insulin secretion by modulating the thiol–disulfide balance that is controlled by the redox signaling in pancreatic β cells.Keywords: endoplasmic reticulum oxidoreductin1, ERO1, geniposide, protein disulfide isomerase, PDI, glucose-stimulated insulin secretion, GSIS, type 2 diabetes mellitus, T2DM